Analysis of Mitochondrial Respiratory Chain Supercomplexes Using Blue Native Polyacrylamide Gel Electrophoresis (BN‐PAGE). Issue 1 (1st March 2016) - Jha, Pooja; Wang, Xu; Auwerx, Johan
Abstract: Mitochondria are cellular organelles that harvest energy in the form of ATP through a process termed oxidative phosphorylation (OXPHOS), which occurs via the protein complexes of the electron transport chain (ETC). In recent years it has become unequivocally clear that mitochondrial complexes of the ETC are not static entities in the inner mitochondrial membrane. These complexes are dynamic and in mammals they aggregate in different stoichiometric combinations to form supercomplexes (SCs) or respirasomes. It has been proposed that the net respiration is more efficient via SCs than via isolated complexes. However, it still needs to be determined whether the activity of a particular SC is associated with a disease etiology. Here we describe a simplified method to visualize and assess in‐gel activity of SCs and the individual complexes with good resolution using blue native polyacrylamide gel electrophoresis (BN‐PAGE). © 2016 by John Wiley & Sons, Inc.